Evaluation of crAssphages as a potential marker of human viral contamination in environmental water and fresh leafy greens - Suh, Soo Hwan; Lee, Jeong Su; Kim, Seung Hwan; Vinjé, Jan; Kim, Soon Han; Park, Geun Woo (Frontiers in Microbiology, 2024)
CrAssphages are human gut bacteriophages with potential use as an indicator of human fecal contamination in water and other environmental systems. We determined the prevalence and abundance of crAssphages in water, food, and fecal samples and compared these estimates with the prevalence of norovirus. Samples were tested using two crAssphage-specific qPCR assays (CPQ056 and TN201-203) and for norovirus using TaqMan realtime RT-PCR. CrAssphage was detected in 40% of human fecal specimens, 61% of irrigation water samples, 58.5% of stream water samples, and 68.5% of fresh leafy greens samples. Interestingly, across all sample categories, crAssphage concentrations were 2-3 log10 higher than norovirus concentrations. The correlation of detection of crAssphage and norovirus was significant for the irrigation water samples (r=0.74, p=7.4e-06). Sequences obtained from crAssphage positive samples from human fecal and stream water samples phylogenetically clustered with genotype I crAssphages, whereas sequences derived from irrigation water samples clustered differently from other genotypes. Our data show that crAssphages were prevalent in norovirus-positive water samples and in fresh leafy greens samples there was a strong correlation between the presence of crAssphage and norovirus. CrAssphage genomic copies were consistently higher than norovirus copies in all sample types. Overall, our findings suggest that crAssphages could be used as reliable indicators to monitor fecal-borne virus contamination within the food safety chain.